Examination of the relationship of governance mechanisms to performance for Singapore listed companies - Ang, Feng Zhi (2008)
This study examines the relationship between monitoring, incentives and ownership structure with financial performance within the constructs of Agency theory. The objective is to examine an array of governance mechanisms and their impact on corporate performance in a sample of firms listed on the Stock Exchange of Singapore.